(Z)-Tetrahydrothiophene and (Z)-tetrahydrothiopyran synthesis through nucleophilic substitution and intramolecular cycloaddition of alkynyl halides and EtOCS2K. Issue 31 (25th July 2019) - Luo, Xianglin; Li, Yibiao; Chen, Xiuwen; Song, Zhiyan; Liang, Junyi; Liao, Chunshu; Zhu, Zhongzhi; Chen, Lu
Abstract : This protocol provides a novel method for the synthesis of ( Z )-tetrahydrothiophene derivatives through the formation of C–S bonds under transition-metal-free condition using thiyl radical intramolecular cycloaddition cascade strategy. Abstract : This protocol provides a novel, environmentally friendly and simple method for the synthesis of ( Z )-tetrahydrothiophene derivatives using the nucleophilic thiyl radical intramolecular cycloaddition cascade process to construct C–S bonds under transition-metal-free conditions. This transformation process offers a broad substrate scope, good functional group tolerance, and excellent stereoselectivity ( Z / E ratios up to 99/1). Moreover, the process uses odourless, stable and cheap EtOCS2 K as the sulfur source.